Currículos nômades nos cotidianos escolares da EJA - Fonseca, Daniele Soares da (2024)
This research is an invitation to search for other ways of thinking and doing curricula in Youth and Adult Education, with strength in collective encounters and experimentation. It starts from the current context marked by attempts to plaster over public education in Brazil, with regard to educational policies that are reflected in the homogenizing and systematizing curricular model, materialized in recent times with the BNCC. We are betting on the possibility of mapping the processes of creating nomadic curricula, conceived as mechanisms for the insurgence of collectivity, which configure errant lines of teaching practices, thoughts and collective bodies in everyday school life. We think of collectivity as the composition of multiplicities that relate intensively. In this sense, collectivity is not seen as an agglutination of individuals, but as a collective agency that is formed from the heterogeneous connections that are established between multiplicities. We used the conceptual tools that address the forms and forces engendered by macro/micro-political movements in education, considering that these movements are incessantly constituted in relation, but the focus of the work is in the field of mechanisms of micro-political forces that weave heterogeneous networks, based on encounters and experiments as collective insurgencies against the plastered curricular model, creating possibilities for inventive teaching-learning actions in everyday school life. It is in this sense that we understand that nomadic curricula constituted from collective experiences create movements of insurgency. Thus, the aim of this research is to follow the movements of the immanent forces that constitute curricula as collective insurgencies, in the teaching modality of Youth and Adult Education, in a school run by the Municipality of Serra/ES. Assuming the post-structuralist epistemological field, the research is based on the Philosophy of Difference in dialog with Deleuze, Guattari, Foucault and many others. It adopts cartography as a methodological approach, which, together with young people and adults, sets out on an incessant wandering along the wandering paths of the inventiveness produced through encounters